Phenotype annotation with the ontology of microbial phenotypes (OMP) - Siegele, Deborah A.; LaBonte, Sandra A.; Wu, Peter I-Fan; Chibucos, Marcus C.; Nandendla, Suvarna; Giglio, Michelle G.; Hu, James C. (Journal of biomedical semantics, 2019)
Microbial genetics has formed a foundation for understanding many aspects of biology. Systematic annotation that supports computational data mining should reveal further insights for microbes, microbiomes, and conserved functions beyond microbes. The Ontology of Microbial Phenotypes (OMP) was created to support such annotation. We define standards for an OMP-based annotation framework that supports the capture of a variety of phenotypes and provides flexibility for different levels of detail based on a combination of pre- and post-composition using OMP and other Open Biomedical Ontology (OBO) projects. A system for entering and viewing OMP annotations has been added to our online, public, web-based data portal. The annotation framework described here is ready to support projects to capture phenotypes from the experimental literature for a variety of microbes. Defining the OMP annotation standard should support the development of new software tools for data mining and analysis in comparative phenomics.